Связь между объемом и площадью шаров в геометрии Гильберта - Борисенко, А.А.; Олин, Е.А. (Видавничий дім "Академперіодика" НАН України, 2008)
We show that the spheres in the Hilbert geometry have the same volume growth rate as those in the Lobachevsky space. We give the asymptotic estimates for the ratio of the volume of a metric ball to the area of a metric sphere in the Hilbert geometry. The derived estimates agree with the well-known facts for the Lobachevsky space.